Psychophysiological responses to repeated-sprint training in normobaric hypoxia and normoxia - Brocherie, F.; Millet, G. P.; Girard, O. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To compare psychophysiological responses to 6 repeated-sprint sessions in normobaric hypoxia (RSH) and normoxia (RSN) in team-sport athletes during a 2-wk "live high-train low" training camp.